Modeling the impact of climate change on water resources case study: Arkansas River Basin in Colorado - Nasr Azadani, Fariborz, author; Fontane, Darrell G., advisor; Grigg, Neil S., committee member; Fitzhorn, Patrick A., committee member (Colorado State University. Libraries, 2012)
There is mounting evidence that amount of carbon dioxide is being increased which can lead to changing the global climate drastically during this century. Climate change can have important effect on the water resources and water demand like urban and agriculture uses. The effects of climate change have been explored in the Arkansas River Basin in Colorado which is one of the major rivers in Colorado that provides water for 650,000 people a year and irrigates around 280,600 acres of agriculture areas. The aim of this research is to project precipitation and temperature in smaller temporal and spatial scale by MAGICC/SCENGEN tool and model the impact of climate change on the water resources by water Evaluation and Planning (WEAP) software to provide results for the water managers and policy makers. Two climate scenarios (A2 and B2) and a 550 ppm policy were used to project future temperature and precipitation in the Arkansas River Basin for the period of 2013 to 2040. Based on the results from the two climate scenarios, a warmer and drier climate is anticipated for the region. Three adaptation scenarios (new irrigation technology scenario, new irrigation technology along with crop change scenario, and new irrigation technology along with reducing crop area scenario) were analyzed to consider their effects to mitigate the negative impact of climate change in the Arkansas River Basin. The results of the simulation of these scenarios showed that all three have a relatively short term impact. This indicates that globe warming is a potentially very serious problem for water management in the Arkansas River Basin.